Resolving the Holocene alluvial record in southeastern Australia using luminescence and radiocarbon techniques - Michael D. Cheetham; Annabelle F. Keene; Wayne D. Erskine; Richard T. Bush; Kathryn Fitzsimmons; Geraldine E. Jacobsen; Stewart J. Fallon (Journal of Quaternary Science, 2010)
A previous assessment of radiocarbon ( 14 C) dates from alluvial units in southeastern Australia revealed a gap in the geochronological record that coincides with the Holocene climatic optimum. This gap in the alluvial record can be further refined using optically stimulated luminescence (OSL). The chronology of Holocene river terraces on Widden Brook, a sandy alluvial stream in southeastern Australia, was established using 14 C and OSL techniques. Combined use of these independent techniques allows for a more rigorous assessment of the alluvial record. The robust chronology, consisting of 38 14 C and 11 OSL samples, permitted identification of significant depositional variation within the catchment, resulting from localised geomorphic processes. The three terrace sequences identified yielded distinct chronologies, suggesting alluvial deposition at different times. The sequences exhibited a continuous chronology, which indicated continuous deposition throughout the Holocene. The chronology of terrace sequences within this catchment suggests that terrace formation can be attributed to localised geomorphic processes rather than climatic forcing. Copyright © 2010 John Wiley & Sons, Ltd.